2015
DOI: 10.1158/2159-8290.cd-14-1113
|View full text |Cite
|
Sign up to set email alerts
|

MYC Drives Pten/Trp53-Deficient Proliferation and Metastasis due to IL6 Secretion and AKT Suppression via PHLPP2

Abstract: We have recently recapitulated metastasis of human PTEN/TP53-mutant PC in mouse using the RapidCaP system. Surprisingly, we found that this metastasis is driven by Myc-, and not Akt-activation. Here, we show that cell-cell communication by Il6 drives the Akt-Myc switch through activation of the Akt-suppressing phosphatase Phlpp2, when Pten and p53 are lost together, but not separately. Il6 then communicates a downstream program of Stat3-mediated Myc-activation, which drives cell proliferation. Similarly in tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 58 publications
(82 reference statements)
4
64
0
Order By: Relevance
“…These include factors that activate Ras-MAPK signaling via cell surface receptors to augment MYC activity, including connective tissue growth factor (39), hepatocyte growth factor (40), and insulinlike growth factor binding proteins 2, 3, and 7 (which signal to EGFR indirectly via sphingosine-1-phosphate) (41). Stromal PSCs also produce Il6, which can activate STAT3 in a paracrine manner to transcriptionally activate MYC (42)(43)(44) and induce associated metabolic and transcriptional changes. We propose that microenvironmental regulation of gene expression cooperates with cellautonomous pathways to fortify cancer cell viability by co-opting an otherwise normal, and usually transient, wound-healing response.…”
Section: Discussionmentioning
confidence: 99%
“…These include factors that activate Ras-MAPK signaling via cell surface receptors to augment MYC activity, including connective tissue growth factor (39), hepatocyte growth factor (40), and insulinlike growth factor binding proteins 2, 3, and 7 (which signal to EGFR indirectly via sphingosine-1-phosphate) (41). Stromal PSCs also produce Il6, which can activate STAT3 in a paracrine manner to transcriptionally activate MYC (42)(43)(44) and induce associated metabolic and transcriptional changes. We propose that microenvironmental regulation of gene expression cooperates with cellautonomous pathways to fortify cancer cell viability by co-opting an otherwise normal, and usually transient, wound-healing response.…”
Section: Discussionmentioning
confidence: 99%
“…PHLPP2, a phosphatase essential for specific and effective termination of oncogenic AKT signaling, was identified as a target gene of miR-181a in the current study [20,21]. PHLPP2, a tumor suppressor that inhibits cell growth and induces apoptosis in cancer cell lines [15], is located at 16q22.3, a region that undergoes loss of heterozygosity (LOH) in breast and ovarian cancers, prostate cancer, and hepatocellular carcinoma [22].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have suggested that IL-6 is a key mediator of the development of metastatic potential in cancer cells (25,26). Previous studies have indicated that IL-6 promotes the initial steps of cancer metastasis, potentially by upregulating MMP-9 through the PI3K/Akt signal pathway (27,28), and it has been demonstrated that IL-6 induces EMT through the expression of molecular markers (29,30). Therefore, the present study evaluated the expression of the primary biomarkers of EMT using western blotting and RT-PCR in SGC7901 cells treated with IL-6.…”
Section: Discussionmentioning
confidence: 99%